Cultivation technology and medicinal properties of the medicinal chamomile (Matric aria chamomilla L.) plant - Xaydarov Mirzoxid; Ibragimova (Zien Journals, 2024)
The article provides information on the biomorphological and systematic analysis of the chamomile medicinal plant, its role in medicine and folk medicine, and the technology of cultivation.
Keywords: Medicinal chamomile; biological properties; inflorescence